2019
DOI: 10.1155/2019/3042108
|View full text |Cite
|
Sign up to set email alerts
|

LyophilizedB. subtilisZB183 Spores: 90-Day Repeat Dose Oral (Gavage) Toxicity Study in Wistar Rats

Abstract: A 90-day repeated-dose oral toxicological evaluation was conducted according to GLP and OECD guidelines on lyophilized spores of the novel genetically modified strain B. subtilis ZB183. Lyophilized spores at doses of 109, 1010, and 1011 CFU/kg body weight/day were administered by oral gavage to Wistar rats for a period of 90 consecutive days. B. subtilis ZB183 had no effects on clinical signs, mortality, ophthalmological examinations, functional observational battery, body weights, body weight gains and food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Zbiotics has added an acetaldehyde dehydrogenase gene that decomposes acetaldehyde in Bacillus subtilis , which can further convert the acetaldehyde converted from ethanol into acetic acid to reduce the harm of alcohol. They used the spores of this strain to conduct a 90-day repeated administration toxicological evaluation on mice, and proved that the bacterium has no side effects [ 67 ]. Zbiotics is the first company in the world to produce and sell genetically engineered probiotic products.…”
Section: Research and Application Of Engineered Probioticsmentioning
confidence: 99%
“…Zbiotics has added an acetaldehyde dehydrogenase gene that decomposes acetaldehyde in Bacillus subtilis , which can further convert the acetaldehyde converted from ethanol into acetic acid to reduce the harm of alcohol. They used the spores of this strain to conduct a 90-day repeated administration toxicological evaluation on mice, and proved that the bacterium has no side effects [ 67 ]. Zbiotics is the first company in the world to produce and sell genetically engineered probiotic products.…”
Section: Research and Application Of Engineered Probioticsmentioning
confidence: 99%
“…Therefore, to combine the benefits of spore resistance and the strong LOX expression in vegetative cells of B. subtilis , we opted to feed mice with a mixture of a combination of a medium dose of 10 8 CFU spores and a high dose of 10 10 CFU vegetative cells per day. This strategy is supported by a recent study showing that feeding rats up to 10 11 CFU/kg body weight spores per day for 90 days did not cause clinically significant side effects [30] . Additionally, for vegetative cells, the dosages varied from 10 4 to 10 10 CFU/ml in the literature [33, 41, 42 .…”
Section: Resultsmentioning
confidence: 79%
“…While PY79 and WB800N are amenable to direct transformation, NCIB3610 and HU58 require phage transduction for genetic manipulation. However, we primarily focused on PY79 in this work because this strain (1) is a widely used strain in laboratory studies with the whole genome sequenced, (2) lacks many mobile genetic elements found in other B. subtilis strains that may confer antibiotic resistance through horizontal gene transfer, (3) has proven safe to vertebrates (e.g., rats, mice, and chickens), and (4) has been genetically modified with specific traits for in vivo applications [30,[32][33][34][35][36] . Importantly, PY79 has been repurposed as probiotics to remove toxic byproducts from alcohol consumption [24] .…”
Section: Genomic Integration Of Lactate Oxidase and Catalase In Multi...mentioning
confidence: 99%
“…In vivo experiments in a mouse model of short‐term alcohol exposure showed that this strain alleviates some features of alcohol liver disease. 34 A similar strain expressing aldehyde dehydrogenase (patent US10849938B2) featured a safe profile in rats 35 and its clinical development is ongoing ( https://zbiotics.com/ ).…”
Section: Engineered Bacteria To Metabolize Toxic Biomoleculesmentioning
confidence: 99%